Simian Virus 40 Small Tumor Antigen Induces Deregulation of the Actin Cytoskeleton and Tight Junctions in Kidney Epithelial Cells - Nunbhakdi-Craig, Viyada (American Society for Microbiology, 2003)
There is increasing evidence that the transforming DNA tumor virus simian virus 40 (SV40) is associated with human malignancies. SV40 small tumor antigen (small t) interacts with endogenous serine/threonine protein phosphatase 2A (PP2A) and is required for the transforming activity of SV40 in epithelial cells of the lung and kidney. Here, we show that expression of SV40 small t in epithelial MDCK cells induces acute morphological changes and multilayering. Significantly, it also causes severe defects in the biogenesis and barrier properties of tight junctions (TJs) but does not prevent formation of adherens junctions. Small t-induced TJ defects are associated with a loss of PP2A from areas of cell-cell contact; altered distribution and reduced amounts of the TJ proteins ZO-1, occludin, and claudin-1; and marked disorganization of the actin cytoskeleton. Small t-mediated F-actin rearrangements encompass increased Rac-induced membrane ruffling and lamellipodia, Cdc42-initiated filopodia, and loss of Rho-dependent stress fibers. Indeed, these F-actin changes coincide with elevated levels of Rac1 and Cdc42 and decreased amounts of RhoA in small t-expressing cells. Notably, these cellular effects of small t are dependent on its interaction with endogenous PP2A. Thus, our findings provide the first evidence that, in polarized epithelial cells, expression of small t alone is sufficient to induce deregulation of Rho GTPases, F-actin, and intercellular adhesion, through interaction with endogenous PP2A. Because defects in the actin cytoskeleton and TJ disruption have been linked to loss of cell polarity and tumor invasiveness, their deregulation by PP2A and small t likely contributes to the role of SV40 in epithelial cell transformation.